FROM CLICKS TO IMPULSE: HOW WEBSITE QUALITY AND E-WOM DRIVE PURCHASES VIA SALES PROMOTIONS - Asmara, Maisa; Sultan, Mokhamad Adib; arissaputra, Rivaldi; Heri Purwanto; Ifa Ratifah, Ifa Ratifah (Jurnal Riset Bisnis dan Manajemen, 2025)
Indonesia's economic growth in the third quarter of 2024 decelerated to 4.95% (yoy), the lowest rate observed over the past year. Despite this, the sector accounted for 61.07% of Gross Domestic Product (GDP), absorbed 97% of the workforce, and contributed 60.4% of total investment. This study explores the relationship between website quality, e-WoM, sales promotion, and impulse buying using a quantitative approach, based on data collected through questionnaires distributed to 300 respondents. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS version 4.0. The results indicated that website quality and e-WoM did not have a direct effect on impulse buying; however, both variables exerted a significant influence on impulse buying when mediated by sales promotion. This study underscores the pivotal role of sales promotion as a mediator that amplifies the impact of website quality and e-WoM on impulse buying decisions, providing valuable insights for MSME actors to formulate more effective marketing strategies.